Design of a triggerable high current switch and modelling of a spark gap - Zuraimy Adzis, 1971- (Skudai : Universiti Teknologi Malaysia, 2001)
Thesis (Master of Engineering (Electrical)) - Universiti Teknologi Malaysia, 2001